The Effect of Modified "Aggression Replacement Training" Program on Self-efficacy of Adolescents with Insulin-dependent Diabetes - Seyed Reza Mazlom; Seyedjavad Hoseini; Hamid Reza Behnam Vashani; Seyedmohsen Asghari Nekah; Aliakbar Raouf Saeb (Mashhad University of Medical Sciences, 2015)
Background: Self-efficacy is a crucial factor in controlling adolescents with insulin-dependent diabetes mellitus (IDDM). Subsequently the negative behavioral reactions such as aggression adversely affect on self-efficacy. Therefore, interventions are essential to reduce the aggression and to improve the self- efficacy in these patients. Aim: To determine the efficacy of the modified "aggression replacement training" program on self-efficacy of adolescents with insulin-dependent diabetes. Methods: In this clinical trial, 70 adult subjects with IDDM who were referred to Parsian Diabetes clinic of Mashhad in 2014 were divided into two groups of intervention and control. The intervention program, including three aspects including: anger control training, social skills training and moral reasoning training was performed in five sessions, each 1.5-2 hours. A five-day interval was between the sessions and each group consisted of 8-10 individuals. The self-management standard questionnaire of "insulin-dependent diabetes management self-efficacy scale (IDMSE)" was filled before the intervention and two months afterwards. Data were analyzed using SPSS version 11.5 with paired and Independent t-tests. Results: In this study, 38.5 and 61.5 percent of the subjects were boys and girls, respectively with total mean age of 15.9±2. The self-efficacy of the subjects before the intervention was not significantly different within the groups (p=0/57). Nevertheless in post-intervention assessment, the self-efficacy of the Intervention group significantly increased (49.0±11.1) compared to the control group (33.7±5.5) (p